Bridging Economics and Religion: Integrating the Strengthening of Sharia Financial Literacy and Religiosity for Muslim Families - Zulfa Hudiyani; Siti Nur Fadzilah; Hemalia Rasyida; Rana Mariyah (TATHO: International Journal of Islamic Thought and Sciences, 2026)
The purpose of this qualitative study is to describe the objectification of religious values among Nahdliyin residents through sharia financial literacy assistance in Bintan Regency, Riau Islands Province. The sources of information in this study are Nahdliyin families, both at the MWCNU, Muslimat NU, and Fatayat NU levels. Secondary data consists of various relevant previous scientific studies. Data collection techniques included observation and interviews. Data analysis was conducted through the stages of reduction, presentation, and verification. The results of the study show the objectification of religious values in the Maslahat Family Programme with Barokah Finance as Family Financial Blessing Training for Nahdliyin in Bintan Regency. The programme contributes to improving literacy and soft skills in sharia-based family financial management as well as strengthening various dimensions of participants' religiosity. This study contributes to the finding that religious-based financial literacy programmes can strengthen financial knowledge and financial piety.